The effect of composition of dietary sugars on hepatic fatty acid synthesis and partitioning and insulin secretion and sensitivity - Low, W (2018)
Increased consumption of foods containing free sugars, especially fructose, has been associated with the development of non-alcoholic fatty liver disease (NAFLD). The overall aim of this thesis is to investigate the effect of composition of fructose and glucose on hepatic fatty acid (FA) synthesis and partitioning and insulin response and to do this, three studies were undertaken. A randomised crossover study was conducted, where subjects consumed a low fructose meal and a high fructose meal with [U13C]palmitate incorporated to trace the metabolic fate of dietary fats. The two study visits were four weeks apart. Overall, it was found that consuming a high fructose meal but not a low fructose one had a marked effect on females but not males in postprandial hepatic FA synthesis and not in hepatic FA partitioning. In the second study, subjects consumed a test meal which contained [U13C]fructose to trace the metabolic fate of dietary fructose. It was demonstrated that though there was fast metabolic conversion of fructose into FAs within 2 hours, less than 1% of the ingested fructose was converted to FAs. A much larger proportion of fructose was oxidised into 13CO2 (30.5%). The objective of the third study was to investigate the acute and chronic effect of high fructose consumption on insulin secretion, liver fat content and hepatic de novo lipogenesis (DNL) in subjects. In the crossover acute arm of the study, single dose consumption of the high fructose drink resulted in significantly lower static insulin secretion rate (ISR) in females but not males. This difference in static ISR diminished following prolonged high fructose consumption. It was also found that the daily consumption of either the low or high fructose drink did not change the liver fat content or fasting hepatic DNL in the subjects. Overall, we found notable gender differences in FA metabolism after consumption of low and high fructose meals, the mechanistic details of which can be investigated in future studies.